2015
DOI: 10.5812/jjhr.22836v2
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Opinion About Euthanasia in East Azerbaijan Province, Iran

Abstract: Objectives:The aim of this study was to investigate the psychometric properties of Rusbult's relationship investment scale based on the main components' analysis, through varimax rotation, and obtaining a precise instrument for Iranian samples. Methods:The statistical population of this study consisted of all 1416 married students of Qazvin Payame Noor University in the academic year of 1396 to 1397, from which 302 subjects were selected by convenience sampling. The statistical population consisted of 300 Paya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 30 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…6 But in Iran, the situation seems different, so that the results of most studies indicated a negative attitude of nurses and other healthcare providers toward euthanasia. 3,[12][13][14][15] In a study that examined the attitude of 382 Iranian nurses, 34% opposed, 24% agreed, and 41.6% had neutral attitudes; 35.3% of nurses accepted active euthanasia and 38.4% agreed with withholding or withdrawal of treatment in passive euthanasia. 17 In the study of Rahimi et al, 14 most nurses who work in Azerbaijan-Iran reported that they are opposed to all aspects of euthanasia and would not participate in the implementation process.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 But in Iran, the situation seems different, so that the results of most studies indicated a negative attitude of nurses and other healthcare providers toward euthanasia. 3,[12][13][14][15] In a study that examined the attitude of 382 Iranian nurses, 34% opposed, 24% agreed, and 41.6% had neutral attitudes; 35.3% of nurses accepted active euthanasia and 38.4% agreed with withholding or withdrawal of treatment in passive euthanasia. 17 In the study of Rahimi et al, 14 most nurses who work in Azerbaijan-Iran reported that they are opposed to all aspects of euthanasia and would not participate in the implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…3,[12][13][14][15] In a study that examined the attitude of 382 Iranian nurses, 34% opposed, 24% agreed, and 41.6% had neutral attitudes; 35.3% of nurses accepted active euthanasia and 38.4% agreed with withholding or withdrawal of treatment in passive euthanasia. 17 In the study of Rahimi et al, 14 most nurses who work in Azerbaijan-Iran reported that they are opposed to all aspects of euthanasia and would not participate in the implementation process. In this study, 77.5% of nurses stated that even if euthanasia is legalized in Iran and accepted by religious leaders, again they will not perform euthanasia for their patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations